The last week : what the gospels teach us about Jesus's final days in Jerusalem - Borg, Marcus J. ([San Francisco] HarperSanFrancisco, 2006)
As scholars Borg and Crossan reacted to questions about the blockbuster film The Passion of the Christ, they discovered that many Christians are unclear on the details of events leading up to the Crucifixion. Here they present a day-by-day account of Jesus's final week of life. They begin their story on Palm Sunday with two triumphal entries into Jerusalem. The first, that of Roman governor Pontius Pilate leading Read more...
Keywords: Jesus Christ -- Biography -- Passion Week. Bible. -- Mark -- Criticism, interpretation, etc. Jesus Christ